Refinements of Reverse Young Inequality for Scalars and Matrices (European Journal of Pure and Applied Mathematics, 2025)
In this article, we introduce some refinements of the reverse young inequality for scalars. As applications of our results, we establish corresponding inequalities for matrices. The obtained inequalities in this article can be viewed as refinements of the derived inequalities by Burqan and Khandaqji [4].
Keywords: Young inequality, positive matrices, unitarily invariant norms, singular values.